Genetic and pharmacological inhibition of microRNA-92a maintains podocyte cell cycle quiescence and limits crescentic glomerulonephritis. Issue 1 (December 2017) - Henique, Carole; Bollée, Guillaume; Loyer, Xavier; Grahammer, Florian; Dhaun, Neeraj; Camus, Marine; Vernerey, Julien; Guyonnet, Léa; Gaillard, François; Lazareth, Hélène; Meyer, Charlotte; Bensaada, Imane; et al.
Abstract Crescentic rapidly progressive glomerulonephritis (RPGN) represents the most aggressive form of acquired glomerular disease. While most therapeutic approaches involve potentially toxic immunosuppressive strategies, the pathophysiology remains incompletely understood. Podocytes are glomerular epithelial cells that are normally growth-arrested because of the expression of cyclin-dependent kinase (CDK) inhibitors. An exception is in RPGN where podocytes undergo a deregulation of their differentiated phenotype and proliferate. Here we demonstrate that microRNA-92a (miR-92a) is enriched in podocytes of patients and mice with RPGN. The CDK inhibitor p57Kip2 is a major target ofmiR-92a that constitutively safeguards podocyte cell cycle quiescence. Podocyte-specific deletion ofmiR-92a in mice de-repressed the expression of p57Kip2 and prevented glomerular injury in RPGN. Administration of an anti-miR-92a after disease initiation prevented albuminuria and kidney failure, indicating miR-92a inhibition as a potential therapeutic strategy for RPGN. We demonstrate that miRNA induction in epithelial cells can break glomerular tolerance to immune injury. Crescentic rapidly progressive glomerulonephritis is a severe form of glomerula disease characterized by podocyte proliferation and migration. Here Henique et al. demonstrate that inhibition of miRNA-92a prevents kidney failure by promoting the expression of CDK inhibitor p57Kip2 that regulates podocyte cell cycle.